(untitled) (Cham, 2015)
This book constitutes the post-proceedings of the 6th International ICST Conference on Mobile Networks and Management, MONAMI 2014, held in Würzburg, Germany, in September 2014. The 22 revised full papers presented were carefully reviewed and selected from 30 submissions. In addition, MONAMI 2014 hosted a workshop on enhanced living environments which also featured 10 papers. The volume is organized thematically in six parts, covering: LTE networks, virtualization and software defined networking, self-organizing networks, energy awareness in wireless networks, wireless networks algorithms and techniques and applications and context-awareness. The workshop on enhanced living environments is organized in thematic sessions on ambient assisted living architectures, human interaction technologies, devises and mobile cloud.
Keywords: Mobile communication systems,Hệ thống thông tin di động; Management,Quản lý